Transitions to democracy a theory of the abnormal? [review of] - Quinio, Emmiline C. (1987)
A review of Guillermo O'Donnell, Phillippe C. Schmitter, Laurence Whitehead, eds., Transitions from Authoritarian Rule: Prospects for Democracy (Baltimore: John Hopkins University Press, 1986), 4 vols.
Keywords: Book reviews; Democracy